2021
DOI: 10.3390/nu13103644
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Amniotic Fluid Metabolic Profile Changes in Response to Gestational Diabetes Mellitus and the Association with Maternal–Fetal Outcomes

Abstract: This study was designed to identify serum and amniotic fluid (AF) metabolic profile changes in response to gestational diabetes mellitus (GDM) and explore the association with maternal–fetal outcomes. We established the GDM rat models by combining a high-fat diet (HFD) with an injection of low-dose streptozotocin (STZ), detected the fasting plasma glucose (FPG) of pregnant rats in the second and third trimester, and collected AF and fetal rats by cesarean section on gestational day 19 (GD19), as well as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
2
3
0
1
Order By: Relevance
“…Among them, p-synephrine and N1-methyl-4-pyridone-3-carboxamide were upregulated, while ginkgolide C was decreased in FGR patients. Consistent with our findings, N1-methyl-4-pyridone-3-carboxamide has been detected in serum and amniotic fluid samples in gestational diabetes mellitus (GDM) patients ( 35 ). Furthermore, a negative correlation between N1-methyl-4-pyridone-3-carboxamide and fetal weight has been reported in those patients involved in nicotinate and nicotinamide metabolism ( 35 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among them, p-synephrine and N1-methyl-4-pyridone-3-carboxamide were upregulated, while ginkgolide C was decreased in FGR patients. Consistent with our findings, N1-methyl-4-pyridone-3-carboxamide has been detected in serum and amniotic fluid samples in gestational diabetes mellitus (GDM) patients ( 35 ). Furthermore, a negative correlation between N1-methyl-4-pyridone-3-carboxamide and fetal weight has been reported in those patients involved in nicotinate and nicotinamide metabolism ( 35 ).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, N1-methyl-4-pyridone-3-carboxamide has been detected in serum and amniotic fluid samples in gestational diabetes mellitus (GDM) patients ( 35 ). Furthermore, a negative correlation between N1-methyl-4-pyridone-3-carboxamide and fetal weight has been reported in those patients involved in nicotinate and nicotinamide metabolism ( 35 ). A recent study showed that ginkgolide C might promote intestinal barrier function and exert anti-inflammatory effects by inhibiting the nuclear factor kappa-light-enhancer of activated B cells (NF-κB) and mitogen-activated protein kinase (MAPK) pathways in a dextran sulfate sodium-induced colitis model ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…It thus is quite biologically plausible that the surgical stress of FLP and the major fluid shifts occurring during the lasering of the placenta would lead to increased consumption of alternative energy sources for the fetus, and the metabolomic profiling in this study captures that acute strain on fetal metabolism. Other high VIP score metabolites, such as choline, are known to play key roles in proper fetal growth and alterations in fetal glucose lead to abnormalities in choline metabolism (Zhou et al, 2021). While amniotic fluid lactate has not been scrutinized during fetal surgery, there has been study of amniotic fluid lactate during labor and specifically abnormal labor.…”
Section: Discussionmentioning
confidence: 99%
“…При этом злокачественная опухоль на фоне СД развивалась гораздо быстрее, нежели в самостоятельном варианте, объемы опухолей нарастали стремительно, продолжительность жизни у самок была меньше. Экспериментальные исследования гестационного диабета показали, что в ответ на внутриутробную среду с высоким содержанием глюкозы плод претерпевает ряд адаптивных изменений, таких как ускорение катаболизма и утилизации глюкозы, что влияет на его рост и развитие [12]. Проводя некоторую параллель между ростом злокачественной опухоли и беременностью, когда как при физиологическом, так и при патологическом процессах происходит «охрана чужого в своем», можно предположить, что злокачественная опухоль, получая дополнительные ресурсы глюкозы, могла существенно ускорить свой пролиферативный потенциал.…”
Section: Discussionunclassified